2022
DOI: 10.1186/s12944-022-01737-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and metabolic alteration involvement in physiotherapy for chronic nonspecific low back pain

Abstract: Background Chronic nonspecific low back pain (cNLBP) is a common health problem worldwide, affecting 65–80% of the population and greatly affecting people’s quality of life and productivity. It also causes huge economic losses. Manual therapy (MT) and therapeutic exercise (TE) are effective treatment options for cNLBP physiotherapy-based treatment. However, the underlying mechanisms that promote cNLBP amelioration by MT or TE are incompletely understood. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Both interventions were conducted for 6 weeks, with three sessions per week. 17 Participants in both groups were not allowed to receive other treatments or a home exercise program during the 6-week intervention period.…”
Section: Methodsmentioning
confidence: 99%
“…Both interventions were conducted for 6 weeks, with three sessions per week. 17 Participants in both groups were not allowed to receive other treatments or a home exercise program during the 6-week intervention period.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that dyslipidemia has been linked to multiple pathological conditions such as cancers, type 2 diabetes, atherosclerosis, liver disease and osteoarthritis [16]. Recently, the association between abnormal lipid metabolism and LBP has also been revealed [17][18][19]. In addition, in vivo and in vitro studies have demonstrated that IDD, as the pathological basis of LBP, could be directly exacerbated by excess cholesterol but could also be alleviated by cholesterol-lowering drugs [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that dyslipidemia has been linked to multiple pathological conditions such as cancers, type 2 diabetes, atherosclerosis, liver disease and osteoarthritis [16]. Recently, the association between abnormal lipid metabolism and LBP has also been revealed [17][18][19]. In addition, in vivo and in vitro studies have demonstrated that IDD, as the pathological basis of LBP, could be directly exacerbated by excess cholesterol but could also be alleviated by cholesterol-lowering drugs [20][21][22].…”
Section: Introductionmentioning
confidence: 99%